Pengaruh Pelatihan, Motivasi, Dan Kepuasan Karyawan Terhadap Kinerja Karyawan Di UD. Rahman (Sidotopo Wetan, Surabaya) - Raynaldy Rizky Rahmawan; Mei Retno Adiwati (JURNAL ILMIAH EDUNOMIKA, 2021)
This research aims to find out the Effect of Training, Motivation, And Employee Satisfaction on Employee Performance. This study used questionnaires that used scoring techniques on likert scale techniques. The sample in this study is that all members of the population are sampled, namely Workers who work in UD. RAHMAN numbered 32 people. Analytical Techniques and Hypothesis Testing Techniques Analysis using PLS (Partial Least Square). The results of this study showed that training does not have a significant influence on employee performance, motivation has a significant effect on employee performance, satisfaction does not have a significant influence on employee performance. Keywords: Effect of Training, Motivation, Employee Satisfaction, Employee Performance